The relation between parents' mental state talk and children's social understanding: A meta‐analysis. Issue 2 (8th January 2018) - Tompkins, Virginia; Benigno, Joann P.; Kiger Lee, Bridget; Wright, Bridget M.
Abstract: Though there is empirical support for the relation between parents' mental state talk to children and children's social understanding, including false belief understanding (FBU) and emotion understanding (EU), effect sizes range widely. The current meta‐analysis focused on the relation between parents' mental state talk and children's social understanding and moderators of this relation: parents' mental state talk content (e.g., cognitive vs. emotion talk), quality (e.g., appropriate vs. inappropriate), and context (e.g., book vs. reminiscing). Data from 22 studies examining FBU and 18 examining EU were examined. Participants included 2, 298 children (<7 years). Analyses yielded a significant effect size for parents' mental state talk and children's FBU and EU. These relations were stronger under certain circumstances, particularly for children's FBU. For example, in terms of content, cognitive state talk was a stronger predictor of FBU and EU compared to talk about desires and emotions. For FBU, the strongest relations were present when parents' mental state talk was: (a) appropriate and explanatory compared to inappropriate and (b) in a book or self‐report context compared to reminiscing. The results of this study further refine the social constructivist view of social understanding and point to future avenues for research aimed at improving children's social understanding.